ampak Ekspor terhadap Ekonomi Indonesia Sebelum dan Selama Pandemi - Umam, Khoirul; Priadana, Sidik; Sidik, Machfud; Subiyantoro, Heru (Neolectura, 2024)
This descriptive quantitative research aims to examine the role of exports in economic growth as reviewed from GDP in 34 provinces in Indonesia. The panel data set comprised 136 observations from 2018 to 2019. The findings indicated that the impact of the pandemic on export performance has been significant, resulting in a notable weakening of economic growth in Indonesia. Consequently, it is imperative for the government to implement a comprehensive policy strategy that prioritises rescue, recovery and prevention from the adverse effects of the pandemic on Indonesia's economic growth and stability